Suhdanne- ja rakennekriisi yhtä aikaa? Toimiala- ja yritysrakenteen muutokset taantumassa - Mika Maliranta; Reijo Mankinen; Paavo Suni (The Research Institute of the Finnish Economy (ETLA), 2011)
The study shows that the exceptional drop in volume of Finland's GDP in 2009 - as much as 8 per cent -was to a large extent due to huge decline in exports and production of one industry, ICT. The contribution of ICT (or electronics and electro-technical industry) to GDP decline was close to two percentage points. The reduction of the industry's value added resulted, again, from the dramatic deterioration of profits (capital income). Nokia is by far the biggest player in the industry (more than half of the value added), and the decline of profits is mainly due to Nokia. Since 80-90 per cent of Nokia's shares is owned by foreigners, the consequences of profit and value added decline are felt mainly outside Finland. Similarly, when the values added and profits grew in the early 2000s, the contribution to GDP growth was overestimated. The reason is that national accounting does not take into account the ownership structure of accumulated retained profits. However, as a result of the crisis the Finnish economy has experienced a permanent decline in its potential production.
Keywords: F23; F43; L63; O47; 330; recession; structural change; profits; employment; productivity